PENGELOLAAN KEUANGAN DESA DALAM PERSPEKTIF MAQASHID SYARIAH (STUDI KASUS DI DESA PONGGOK, KECAMATAN POLANHARJO, KABUPATEN KATEN): CASE STUDY AT PONGGOK VILLAGE, POLANHARJO SUBDISTRICT, KLATEN DISTRICT - Febrianto, Nur Fitroh (Sekolah Tinggi Ilmu Syariah Husnul Khotimah, 2021)
The development of a village is certainly carried out by various aspects of the field. This is of course supported through regulations concerning village autonomy and village fund assistance. In addition, regional development in Islam should be able to present Maqashid Syariah. so that, this indicator is very important for research. This research discusses village financial management based on of The Regulation of Ministry of Internal Affairs of the Republic of Indonesia no. 20 the Year 2018. Meanwhile, Maqashid Syariah is based on the theory put forward by Syathibi. The results of this study certainly can be used as a reference for other villages so that village financial management is in line with development in Islam. The Management of Village Finances, Maqashid Syariah.